The Effect of Online Learning on Student Learning Outcomes in Indonesian Subjects - Abdul Hakim; Nurhikmah H Nurhikmah; Nur Halisa; Farida Febriati; Latri Aras; Lutfi B Lutfi (Journal of Innovation in Educational and Cultural Research, 2023)
This study employs a Pre-Experimental Design (Non-design) to examine whether online learning has any effect on learning outcomes in Indonesian subjects. The sample size for this study was 16 students, chosen at random. Data collection methods include observation, testing, and documentation. Observations were made by observing both teacher and student activities. The test consists of a pretest before implementing offline learning and a posttest after implementing online learning, as well as documentation for research purposes. The data was analyzed using descriptive statistics and the non-parametric Wilcoxon signed ranks test (Z). The average value of student learning outcomes in an Indonesian class after offline learning was higher than after online learning, according to the results of the non-parametric Wilcoxon signed ranks test (Z) processed using SPSS 22 for windows. The findings revealed that the effect of online learning on learning outcomes in an Indonesian course after implementing offline learning is greater than the effect of online learning after implementing offline learning. The findings reveal that the effect of online learning on learning outcomes in an Indonesian language subject after implementing offline learning is greater than the effect of online learning after implementing offline learning. It is possible to conclude that online learning has an effect on students' learning outcomes in Indonesian Class IV subjects at SD Negeri 1 Bonto-Bonto, Pangkep Regency.